Farm.ink Digital Learning Platform - CGIAR Platform for Big Data in Agriculture (2019)
In 2019 we completed work on the new web platform that translates the successful features of the prior farm.ink chatbot and group products to a more accessible, powerful and feature-rich platform for farmers. In this report we share our key findings as we designed, tested and built this new platform.